ANALISIS SEKTOR UNGGULAN DAN PENYERAPAN TENAGA KERJA DI KABUPATEN LOMBOK TENGAH TAHUN 2014 – 2018 - muhamad Sayuti; Wenny Rosita Safitri (JURNAL KOMPETITIF : MEDIA INFORMASI EKONOMI PEMBANGUNAN, MANAJEMEN DAN AKUNTANSI, 2020)
Leading/base economic sectors in a region are sectors that have higher production capability compared to the ability of the same sector in other regions, thus the leading/base economic sector products and services aside from being able to meet their own needs, the rest can be sold outside the region so that the region receives income. The study aims to find out what sectors are the leading sectors in Central Lombok Regency and which leading sectors absorb the largest worforce in Central Lombok Regency. The scope of this study is leading sectors and labor. Data analysis using the Location Quotient (LQ) analysis method. Then the general conclusions drawn and accountable. The results of this study indicate that based on the results of the Location Qoutient (LQ) analysis for 2014-2018 in terms of the role of the ceonomic sectors in Central Lombok Regency, there are 10 (ten) leading/base sectors (LQ > 1) including: Manufacturing Industry Sector; Transportation and Warehousing Sector; Water Cuplay, Waste, Waste and Recyling Management Sector; Construction Sector; Health Services and Social Activities Sector; Real Estate Sector; Agriculture, Forestry and Fisheries Sector; Outher Service Sector; Government Administration, Defense and Mandatory Social Security Sector; and the Education Services Sector. While the results of the Location Quotient (LQ) analysis in terms of the proportion of the main business field, the employment in Central Lombok Regency which gives a higher role (LQ < 1), namely Agriculture Sector and the Industrial Sector.